Cytidine acetylation yields a hypoinflammatory synthetic messenger RNA. Issue 2 (17th February 2022) - Nance, Kellie D.; Gamage, Supuni Thalalla; Alam, Md Masud; Yang, Acong; Levy, Michaella J.; Link, Courtney N.; Florens, Laurence; Washburn, Michael P.; Gu, Shuo; Oppenheim, Joost J.; Meier, Jordan L.
Summary: Synthetic messenger RNA (mRNA) is an emerging therapeutic platform with important applications in oncology and infectious disease. Effective mRNA medicines must be translated by the ribosome but not trigger a strong nucleic acid-mediated immune response. To expand the medicinal chemistry toolbox for these agents, here we report the properties of the naturally occurring nucleobase N 4 -acetylcytidine (ac4C) in synthetic mRNAs. We find that ac4C is compatible with, but does not enhance, protein production in the context of synthetic mRNA reporters. However, replacement of cytidine with ac4C diminishes inflammatory gene expression in immune cells caused by synthetic mRNAs. Chemoproteomic capture indicates that ac4C alters the protein interactome of synthetic mRNAs, reducing binding to cytidine-binding proteins and an immune sensor. Overall, our studies illustrate the unique ability of ac4C to modulate RNA-protein interactions and provide a foundation for using N 4 -cytidine acylation to fine-tune the properties of nucleic acid therapeutics. Graphical abstract: Highlights: N 4 -acetylcytidine (ac4C) incorporated into synthetic eGFP messenger RNAs (mRNA) Synthetic ac4C mRNAs produce comparable eGFP as modified/unmodified mRNAs Synthetic ac4C mRNAs are less inflammatory in immune cells than cytidine mRNAs Cytidine acetylation alters the protein interaction landscape of synthetic mRNAs Abstract : Messenger RNA (mRNA) therapeutic platforms benefit from nucleotide components that enable protein translation while evading immune activation. Here, Nance et al. report the exploration of N 4 -acetylcytidine (ac4C) as a medicinal chemistry element in a synthetic mRNA.